Endotyping Seasonal Allergic Rhinitis in Children: A Cluster Analysis - Malizia, Velia; Ferrante, Giuliana; Cilluffo, Giovanna; Gagliardo, Rosalia; Landi, Massimo; Montalbano, Laura; Fasola, Salvatore; Profita, Mirella; Licari, Amelia; Marseglia, Gian Luigi; La Grutta, Stefania (Frontiers in Medicine, 2022)
Background: Seasonal Allergic Rhinitis (SAR) is a heterogeneous inflammatory disease. We hypothesized that a cluster analysis based on the evaluation of cytokines in nasal lavage (NL) could characterize distinctive SAR endotypes in children. Methods: This cross-sectional study enrolled 88 children with SAR. Medical history, quality of life Paediatric Rhinoconjunctivitis Quality of Life Questionnaire (PRQLQ) and sleep quality Pittsburgh Sleep Quality Index (PSQI) were assessed through standardized questionnaires. Children were grouped through K-means clustering using Interleukin (IL)-5, IL-17, IL-23, and Interferon (INF)-γ in NL. Results: Out of the 88 patients enrolled, 80 were included in the cluster analysis, which revealed three SAR endotypes. Cluster 1 showed lower levels of IL-5 and IL-17 and intermediate levels of IL-23 and IFN-γ; Cluster 2 had higher levels of IL-5 and intermediate levels of IL-17, IL-23, and IFN-γ; Cluster 3 showed higher levels of IL-17, IL-23, and IFN-γ and intermediate levels of IL-5. Cluster 1 showed intermediate values of nasal pH and nasal nitric oxide (nNO), and a lower percentage of neutrophils at nasal cytology than Clusters 2 and 3. Cluster 2 had a lower level of nasal pH, a higher nNO, higher scores in the ocular domain of PRQLQ, and worse sleep quality than Clusters 1 and 3. Cluster 3 showed a higher percentage of neutrophils at nasal cytology than Clusters 1 and 2. Conclusions: Our study identified three endotypes based on the evaluation of cytokines in NL, highlighting that childhood SAR is characterized by heterogeneous inflammatory cytokines.